Novel insight into the therapeutical potential of flavonoids from traditional Chinese medicine against cerebral ischemia/reperfusion injury - Zhou, Jing; Sun, Feiyue; Zhang, Wenli; Feng, Zhitao; Yang, Yi; Mei, Zhigang (Frontiers in Pharmacology, 2024)
Cerebral ischemia/reperfusion injury (CIRI) is a major contributor to poor prognosis of ischemic stroke. Flavonoids are a broad family of plant polyphenols which are abundant in traditional Chinese medicine (TCM) and have beneficial effects on several diseases including ischemic stroke.Accumulating studies have indicated that flavonoids derived from herbal TCM are effective in alleviating CIRI after ischemic stroke in vitro or in vivo, and exhibit favourable therapeutical potential.Herein, we systematically review the classification, metabolic absorption, neuroprotective efficacy, and mechanisms of TCM flavonoids against CIRI. The literatures suggest that flavonoids exert potential medicinal functions including suppressing excitotoxicity, Ca 2+ overloading, oxidative stress, inflammation, thrombin's cellular toxicity, different types of programmed cell deaths, and protecting the blood-brain barrier, as well as promoting neurogenesis in the recovery stage following ischemic stroke. Furthermore, we identified certain matters that should be taken into account in future research, as well as proposed difficulties and opportunities in transforming TCM-derived flavonoids into medications or functional foods for the treatment or prevention of CIRI. Overall, in this review we aim to provide novel ideas for the identification of new prospective medication candidates for the therapeutic strategy against ischemic stroke.